Dental and craniofacial manifestations in sponastrime dysplasia - An observational study - Arponen, Heidi; Valta, Helena; Mäkitie, Outi (Bone (New York, N.Y.), 2025)
Sponastrime dysplasia is an extremely rare autosomal recessive spondyloepimetaphyseal dysplasia characterized by short stature, midface hypoplasia, nasal alterations, and dental anomalies. This is, to date, the first comprehensive report on oral and craniofacial findings, and on subjective oral health-related quality of life as clinically and radiologically examined in two adults with sponastrime dysplasia. Both subjects had typical features of sponastrime dysplasia with disproportionate short stature, hypertelorism and midface hypoplasia, and variants in the TONSL gene. One had a severe phenotype (adult height 91 cm), whereas the other exhibited moderate severity (adult height 135 cm). The notable variation in the disorder severity was also expressed in dental manifestations. Dentin dysplasia type I-like abnormalities were seen in tooth eruption and morphology. Dental roots were shortened in both individuals. The individual with severe growth failure had lost several permanent teeth and reported a moderate level of discomfort and impairment due to oral health issues, as evaluated with the Oral Health Impact Profile questionnaire. In contrast, the other individual had a full permanent dentition and minimal negative impact on oral health-related quality of life. Both had short jaw lengths and face height. The anteroposterior jaw relationships were normal. The jaws of the individual with a severe phenotype were retrognathic in relation to the skull base. Both had prominent forehead. Due to significant craniofacial and dental involvement, individuals with sponastrime dysplasia should be regularly followed by a multidisciplinary medical team including a dentist, to maintain individuals' oral health and oral health-related quality of life. •Sponastrime dysplasia is an ultra-rare spondyloepimetaphyseal dysplasia.•Individuals with sponastrime dysplasia might experience early loss of teeth due to short roots.•Mutations of the TONSL gene can lead to dentin dysplasia type I -like dental phenotype.•Variation in the disorder severity seems to be expressed also in gravity of dental manifestations.